Les marais salants brésiliens entre protection environnementale et pression foncière : un paysage en mutation - Vanessa Moura de Lacerda Teixeira (Projets de Paysage)
This article reflects on the aspects of salt marsh landscapes threatened by the continued expansion of the real estate sector. In seeking to develop real estate assets some decision makers consider salt marshes as a potential land source for urban development. Two methodologies are put forward to conduct a critical examination of environmental policies and their effects on the salt marsh landscape. On the one hand, the evolution of the salt marsh landscape illustrated by means of historical photographs and the study of land use through maps representing successive spatial transformations; and on the other hand, local policies, namely certain laws approved by municipalities which help to address the problem of the disappearance of salt marshes and their environmental protection. The results of this study demonstrate that the land tenure of these salt marshes has been the object of a great deal of pressure due to the discontinuation of salt production in favour of building and real estate development.